Early tumour response as a survival predictor in previously- treated patients receiving triplet hepatic artery infusion and intravenous cetuximab for unresectable liver metastases from wild-type KRAS colorectal cancer. (November 2016) - Bouchahda, Mohamed; Boige, Valérie; Smith, Denis; Karaboué, Abdoulaye; Ducreux, Michel; Hebbar, Mohamed; Lepère, Céline; Focan, Christian; Guimbaud, Rosine; Innominato, Pasquale; Awad, Sameh; Carvalho, Carlos; et al.
Abstract: Background: Early tumour shrinkage has been associated with improved survival in patients receiving cetuximab-based systemic chemotherapy for liver metastases from colorectal cancer (LM-CRC). We tested this hypothesis for previously treated LM-CRC patients receiving cetuximab (500 mg/m 2 ) and triplet hepatic artery infusion (HAI) within European trial OPTILIV. Methods: Irinotecan (180 mg/m 2 ), 5-fluorouracil (2800 mg/m 2 ) and oxaliplatin (85 mg/m 2 ) were given as chronomodulated or conventional delivery. Patients were retrospectively categorised as early responders (complete or partial RECIST response after three courses) or non-early responders (late or no response). Prognostic factors were determined using multivariate logistic or Cox regression models. Results: Response was assessed in 57 of 64 registered patients (89%), who had previously received one to three prior systemic chemotherapy protocols. An early response occurred at 6 weeks in 16 patients (28%; 9 men, 7 women), aged 33–76 years, with a median of 12 liver metastases (LMs) (2–50), involving five segments (1–8). Ten patients had a late response, and 31 patients had no response. Grade 3–4 fatigue selectively occurred in the non-early responders (0% versus 26%; p = 0.024). Early tumour response was jointly predicted by chronomodulation—odds ratio (OR): 6.0 (1.2–29.8; p = 0.029)—and LM diameter ≤57 mm—OR: 5.3 (1.1–25.0; p = 0.033). Early tumour response predicted for both R0-R1 liver resection—OR: 11.8 (1.4–100.2; p = 0.024) and overall survival—hazard ratio: 0.39 (0.17–0.88; p = 0.023) in multivariate analyses. Conclusions: Early tumour response on triplet HAI and systemic cetuximab predicted for complete macroscopic liver resection and prolonged survival for LM-CRC patients within a multicenter conversion-to-resection medicosurgical strategy. Confirmation is warranted for early response on HAI to guide decision making. Protocol numbers : EUDRACT 2007-004632-24 NCT00852228 . Highlights: The rate of conversion-to-resection of liver metastases was tripled after early tumour response. The median overall survival of early responders was 14 months longer than that of the late or non-responders. Early response on hepatic artery infusion should critically optimise curative intent medicosurgical strategies.